A REVOLUÇÃO RUSSA E OS MOVIMENTOS DE RESISTÊNCIA NA AMÉRICA LATINA - Joana Aparecida Coutinho (Universidade Federal do Maranhão, 2018)
This text discusses the influences of the Russian Revolution of 1917 on resistance movements in Latin America. Seeks to reflect how the experience of the October Socialist Revolution of 1917 rekindled the hopes of Revolutions in Latin America fed and raised anti-capitalist and imperialist resistance movements on the continent.